Moeda, Estado e poder : limites dos Direitos Especiais de Saque enquanto alternativa ao dólar como moeda-chave - Martins, Aline Regina Alves, 1984- (2014)
Orientadores: Reginaldo Carmello Corrêa de Moraes, Carlos Eduardo Ferreira de Carvalho